Association of serum chloride levels with all-cause mortality among patients in surgical intensive care units: a retrospective analysis of the MIMIC-IV database - Quan Ma; Wei Tian; Kaifeng Wang; Bin Xu; Tianyu Lou (BMC Anesthesiology)
Abstract This study explores the association between serum chloride concentrations and all-cause mortality among patients in the Surgical Intensive Care Unit (SICU). Employing a retrospective cohort design, the study utilized data extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, specifically focusing on individuals admitted to the surgical/trauma ICUs. This dataset encompassed demographic profiles, laboratory findings, historical medical data, vital statistics, and variables pertinent to prognosis. Participants were divided into four groups based on their serum chloride concentrations. The primary outcomes assessed were mortality rates at 30, 90, and 180 days post-admission to the ICU. Analytical methods included Kaplan–Meier survival curves, Cox proportional hazards regression models, and Restricted Cubic Spline (RCS) analyses to delineate the relationship between serum chloride concentrations and patient outcomes. The study cohort comprised 10,996 patients, with observed mortality rates of 12.78% at 30 days, 17.14% at 90 days, and 20.32% at 180 days. Kaplan–Meier analyses revealed significant disparities in survival rates across the quartiles of serum chloride during the follow-up intervals (p < 0.001). The results from the multivariable Cox regression suggested a substantial inverse association between high serum chloride levels and decreased mortality at 30 days (hazard ratio [HR]: 0.96; 95%confidence interval [CI]: 0.95–0.97; P < 0.001), 90 days (HR: 0.97; 95% CI: 0.96–0.98; P < 0.001), and 180 days (HR: 0.97; 95% CI: 0.96–0.98; P < 0.001). Particularly, patients in the highest quartile of serum chloride faced significantly lower mortality risks compared to those in the lowest quartile (30 days HR = 0.65, 90 days HR = 0.71, 180 days HR = 0.69, P < 0.001). RCS analysis depicted an L-shaped curve demonstrating the dynamics between serum chloride concentrations and the risk of all-cause mortality across the 30-day, 90-day, and 180-day periods.Starting at a concentration of 104 mmol/L, a decrease in serum chloride levels was associated with an increased risk of mortality.These findings elucidate a marked nonlinear association between serum chloride levels and all-cause mortality in SICU patients, enhancing our comprehension of serum chloride’s impact on clinical outcomes in this setting.